2021
DOI: 10.1111/tpj.15256
|View full text |Cite
|
Sign up to set email alerts
|

Altered chromatin conformation and transcriptional regulation in watermelon following genome doubling

Abstract: Polyploidy has played a crucial role in plant evolution, development and function. Synthetic autopolyploid represents an ideal system to investigate the effects of polyploidization on transcriptional regulation. In this study, we deciphered the impact of genome duplication at phenotypic and molecular levels in watermelon. Overall, 88% of the genes in tetraploid watermelon followed a >1:1 dosage effect, and accordingly, differentially expressed genes were largely upregulated. In addition, a great number of hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 74 publications
(90 reference statements)
1
8
0
Order By: Relevance
“…Detaching from the NL and moving inside the nucleus, LADs contribute to the opening of chromatin [ 123 ]. This is in agreement with the fact that the upregulation is stronger than the downregulation in the ploidy-associated changes in gene expression [ 126 ].…”
Section: Ploidy-associated Transcriptome Features Are Related To Stre...supporting
confidence: 88%
See 1 more Smart Citation
“…Detaching from the NL and moving inside the nucleus, LADs contribute to the opening of chromatin [ 123 ]. This is in agreement with the fact that the upregulation is stronger than the downregulation in the ploidy-associated changes in gene expression [ 126 ].…”
Section: Ploidy-associated Transcriptome Features Are Related To Stre...supporting
confidence: 88%
“…Accordingly, the association between polyploidy and chromatin decompactization under stress was well documented for cardiomyocytes and hepatocytes [ 76 , 128 ]. At the lower levels of genome organization, polyploidy can alter global patterns of DNA methylation, microRNA expression, and histone modification in mammal, insect, and plant cells [ 1 , 2 , 98 , 126 , 129 , 130 ]. Polyploid cells show higher expression of bivalent genes, which harbor both activating (H3K4me3) and repressive (H3K27me3) chromatin domains [ 78 , 112 ].…”
Section: Ploidy-associated Transcriptome Features Are Related To Stre...mentioning
confidence: 99%
“…In watermelon, in addition to a larger fruit size, the leaves, stem width, and staminate flowers of tetraploid watermelon (CLT1) were larger than those of diploid plants (CLD1) [ 31 ]. In another study, it was found that chromosome doubling enhanced seed size, cotyledon size, stem thickness, and trichome density and length [ 32 ]. Furthermore, there were differences in lycopene and hormone content between tetraploid and diploid watermelon during the fruit development stage; tetraploid watermelon contained more lycopene and IAA than the diploid genotype [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin regions transitioning from B to A are strongly enriched for heart developmental genes upregulated during human and mouse cardiogenesis and in cardiac differentiation of hPSCs [ 105 ]. Accordingly, data obtained from synthetic autotetraploid plants (watermelon, soybean, and Arabidopsis) also indicate that polyploidy shifts the A-to-B chromatin balance toward the actively transcribed A-chromatin [ 106 , 107 ]. Moreover, recent studies provide evidence that genome duplications reorganize topologically associated domains (TAD) packaged within A- and B-chromatin compartments via the increase in intra-TAD interaction and reorganization of chromatin loops [ 106 , 108 ].…”
Section: Myc and Polyploidy Promote Chromatin Openingmentioning
confidence: 99%